Women's Empowerment, Sibling Rivalry, and Competitiveness : Evidence from a Lab Experiment and a Randomized Control Trial in Uganda - Buehren, Niklas (World Bank, Washington, DC, 2016)
This study looks at how a community event—adolescent women's economic and social empowerment -- and a family factor -- sibling sex composition—interact in shaping gender differences in preferences for competition. To do so, a lab-in-the-field experiment is conducted using competitive games layered over the randomized rollout of a community program that empowered adolescent girls in Uganda. In contrast with the literature, the study finds no gender differences in competitiveness among adolescents, on average. It also finds no evidence of differences in competitiveness between girls in treatment and control communities, on average. However, in line with the literature, in control communities the study finds that boys surrounded by sisters are less competitive. Strikingly, this pattern is reversed in treatment communities, where boys surrounded by (empowered) sisters are more competitive.